Growth of pruned eucalypt clone in an agroforestry system in southeastern Brazil - Fontan, Ivan C. I.; Reis, Geraldo G.; Reis, Maria G. F.; Leite, Helio G.; Monte, Marco A.; Ramos, Diêgo C.; Souza, Felippe C. (Agroforestry Systems, 2011)
This study aimed to identify pruning intensity and frequency that can be applied to eucalypt without imposing growth reduction, in an agroforestry system in Brazil (17°36’ S and 46°42’ W). Pruning treatments included removal of 0, 1/4 and 1/3 of the live crown height (LCH) with or without the removal of some thick branches above this height (TBA), in three or four lifts, which started at 9 months. There was no effect of pruning on tree height. Diameter (dbh) and volume per tree decreased (P ≤ 0.05) only with the removal of 1/3 of the LCH + TBA, of all trees of the stand, in three lifts, up to 36 months. The Weibull diameter distribution curves showed a higher proportion of trees in the greatest diameter classes with the removal of 1/4 or 1/3 of the LCH + TBA of selected trees, in four lifts, at the age of 36 months. The time required for applying pruning to a height of 6 m did not differ among treatments (P > 0.05). Pruning up to 1/3 of the LCH + TBA of selected trees, in 4 lifts (6-month intervals) is recommended because there was a higher proportion of trees in the greatest diameter classes and the dbh at the time of the last pruning was smaller than for the other treatments, which implies in reduced knotty core. The production of trees with larger diameter and reduced knotty core may increase farmers’ income and reduce the pressure on native forests.
Keywords: Green crown pruning; Multiproduct; Plant growth; Silvopastoral system